(untitled) (Journal of the College of Basic Education, 2022)
The concept of visual attraction is one of the important topics in the institutions of interior designs and in the processes of building structures that refer to a performance organization, including the relationships between components to achieve a level of functional and aesthetic performance, as a group that interacts with each other, and we single out visual attraction to play an effective role in terms of natural and industrial requirements organizational and at the level of the method of effective performance of all. Realized by this interaction in relationships